INFLUENCE OF CATTLE PRODUCTION TYPE TO INVESTMENTS IN CONTEMPORARY HOUSING AND EQUIPMENT (RESULTS OF QUESTIONNAIRE) - Sanjin Ivanović; Lana Ivanović; Sinisa Bratić (Ekonomika Poljoprivrede (1979), 2008)
Family farms play the most important role in cattle production in Republic of Serbia. These farms are dealing with different types of cattle production, and each production type requires different structure of investments. Questionnaire that involved family farms indicated that some farms invest more in cattle housing, but other farms invest more in modern equipment.